(3MGTjI Ydi TQM GdYbGFO GdfSajIs - (3GdNjGdj, CMeO Hf ehSi, J (B862 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; bGd GdTGQM GdfMQjQ YGedg Gddg JYGdi HdWag GdNWjQ HYO eGJjef HGdJSejI GdMeL ddg Cbhd aj JYbjH GdJSejI HGdJMejO GbJOGA HCSdhH GdcJGH GdeLjOs
(3BNQgG (B:s
(3bhdg gPG GdEOYGA eG dG ojbHd aj Mb GdCfHjGA hHg jXgQ Gf gPG GdhLg CjV jbjO JaVdge abW hCf GdaVd Hd Gddg JYGdi jDJjg ef jTGA hGddg Ph GdaVd GdYXjes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 262s
(3eYLe GdeDdajf (B1 / 315s
(3cTa GdXfhf (B2 / 1145s
(3T (B7 / 343s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds